Workplace sexual harassment toward male nurses in South Korea: a cross-sectional online survey - Suyong Jeong; Hyoung Eun Chang (BMC, 2022)
Abstract Background Many studies have focused on sexual harassment of female nurses perpetrated by patients and coworkers. However, as males in a female-dominated occupation, male nurses are also at risk of being exposed to sexual harassment. The aim of this study was to examine the prevalence of workplace sexual harassment faced by male nurses in South Korea and to identify related factors. Methods A cross-sectional study was conducted using an online survey that recruited male nurses working in various general hospitals in South Korea. In total, 246 participants with at least 6 months of clinical experience enrolled in an online survey, and 155 male nurses were included in the final analysis. Data were collected from May 31, 2019 to July 26, 2020. Items on the questionnaire included sexual harassment experiences, nursing work environment, and general characteristics of the participants. Descriptive statistics were used to analyze participants' general characteristics and a negative binomial regression model was used to analyze predictors of workplace sexual harassment. Results The mean number of sexual harassment incidents was 3.2 ± 5.5. The majority (65.2%) of male nurses had experienced sexual harassment at least once at work. The negative binomial regression model in the study was found to be acceptable (likelihood ratio chi-square = 30.03, df = 18, p = .037). The perceived nursing work environment was the only significant predictor of sexual harassment towards male nurses (p = .001; incidence rate ratio = 0.37; 95% CI, 0.20-0.66). Conclusions Nursing administrators must recognize that men in female-dominated occupation may experience sexual harassment in the workplace. Specific and realistic managerial policies and educational programs should be implemented to prevent workplace sexual harassment and improve the nursing work environment for male nurses.